2020
DOI: 10.30703/cije.643239
|View full text |Cite
|
Sign up to set email alerts
|

Türkçe Öğretmeni Adaylarının Akademik Erteleme Davranışları ile Akademik Öz Yeterlikleri Arasındaki İlişkinin İncelenmesi

Abstract: Bu araştırmanın amacı, Türkçe öğretmeni adaylarının akademik erteleme davranışları ve akademik öz yeterlikleri ile ilgili görüşleri arasındaki ilişkiyi belirlemektir. Çalışmada ilişkisel tarama modeli kullanılmıştır. Araştırmanın örneklemini Türkiye İstatistik Kurumu (TÜİK) tarafından ortaya konan istatistiki bölge birimlerinden seçilen 13 ilde bulunan devlet üniversitelerindeki eğitim fakültelerinin Türkçe öğretmenliği programlarında 2017-2018 eğitim-öğretim yılında öğrenim görmekte olan 4. sınıf öğrencisi 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…It can be said that as students' academic procrastination behavior decreases, their problematic internet usage levels will decrease. Şengül and Seyfi (2020) attempted to determine the relationship between the views of preservice teachers on academic procrastination behavior and academic self-efficacy. When the relationship between academic procrastination behavior and academic self-efficacy was examined in the findings of the study, it was concluded that there was a low negative relationship.…”
Section: Discussionmentioning
confidence: 99%
“…It can be said that as students' academic procrastination behavior decreases, their problematic internet usage levels will decrease. Şengül and Seyfi (2020) attempted to determine the relationship between the views of preservice teachers on academic procrastination behavior and academic self-efficacy. When the relationship between academic procrastination behavior and academic self-efficacy was examined in the findings of the study, it was concluded that there was a low negative relationship.…”
Section: Discussionmentioning
confidence: 99%
“…One of the key elements of being successful in our daily life is to accomplish the tasks or things we need to do on time. However, especially today, it is seen that individuals postpone what they need to do to other times for different reasons, even though they have the time, opportunity or energy to work (Şengül & Seyfi, 2020). It is seen that not only students but also almost everyone postpones their daily tasks or work.…”
Section: Introductionmentioning
confidence: 99%
“…Üniversite öğrencilerinin akademik erteleme davranışlarının düzeyi, sebepleri ve bazı değişkenlerle ilişkisi konusunda araştırmalar (Bayrak, 2018;Mişe & Hançer, 2019;Sarıkaya Aydın & Koçak, 2016;Şengül & Seyfı̇, 2020) bulunmasına rağmen din eğitimi alanında bu konuda tespit edilebilen tek çalışma Aktaş (2021) tarafından yapılan araştırmadır. Aktaş, araştırmasında Gümüşhane Üniversitesi İlahiyat Fakültesi örnekliğinden hareketle, yüksek din öğretimi gören öğretmen adaylarının akademik erteleme davranışıyla gelecek zaman algısı arasındaki ilişkiyi incelemiştir.…”
Section: Introductionunclassified